Pendidikan Karakter Sebagai Fondasi Pengembangan Kompetensi Sosial SDM Pendidikan: Membangun Ekosistem Sekolah yang Humanis dan Kolaboratif - Sunarso, Budi; Suryanti, Jasi; Wahyuningsih, Endang Sri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to critically analyze the contribution of character education in shaping the social competence of educational human resources and its implications for the development of a humanistic and collaborative school ecosystem. The method employed is a literature review with a qualitative approach and descriptive analysis, using 38 selected scholarly articles published between 1977 and 2025 sourced from Google Scholar and other credible academic platforms. The findings reveal that character education serves as an essential foundation in cultivating social competencies such as empathy, communication, and collaboration—prerequisites for healthy interaction within educational environments. These findings are supported by various theories, including Character Education Theory, Social Learning Theory, and Ecological Systems Theory, as well as case studies demonstrating the successful integration of character values in creating inclusive and democratic school environments. The implications of this research point to the urgent need for policy reforms and school management practices that place character at the core of systemic educational human resource development.